The Effect of Moral Disengagement on Bullying: Testing the Moderating Role of Personal and Social Factors - Travlos, Antonios K. (Journal of interpersonal violence, 2021)
Bullying is a subset of aggressive behavior that has severe consequences in children’s psychosocial development. Bullying behaviors can be influenced by personal and social factors, such as gender, age, school type, and sport participation, as well as psychological constructs, such as moral disengagement. The present study was designed to investigate the effect of moral disengagement on bullying behaviors and the moderating role of personal and social factors. In this study, 2,252 students (M = 13.57, SD = 1.17; 1,125 girls, and 1,127 boys) attending the sixth grade of primary school and secondary education have participated. Participants completed the revised Olweus Bully/Victim Questionnaire and Bandura’s Moral Disengagement Questionnaire along with general questions about their demographic characteristics. The results of the analyses demonstrated moderation effects of gender on the moral disengagement–physical bullying relationship and of age on the moral disengagement–verbal bullying relationship. No significant moderating effect emerged for school type and sport participation. The findings of the present study provide valuable information about the role of personal and social factors on bullying behavior.